More To What Meets The Eyes: Myopericytoma Of The Preauricular Sinus - Azlina Ab Rani; Goh Bee See; Nordashima Abdul Shukur; Noor’Ain Mohd Nasir (Taylor & Francis Online, 2024)
Preauricular lesions such as cysts, pits, fissures are congenital malformations of the preauricular soft tissues. These lesions are common and seen in the paediatric population, located near the anterior aspect of the ear. Surgical excision of the lesion would usually be performed if the lesion is infected to avoid multiple episodes of infection. We report a case of a 9-year-old boy who presented with a lesion of the preauricular area. It was excised due to enlargement of the lesion over time. Histopathological examination revealed the lesion to be a rare myopericytoma of the preauricular sinus. In this report, we discuss regarding this rare soft tissue lesion with regards to the head and neck region.